Corporate entrepreneurship and sustainability : a case study collection - Cheah, Sarah Lai-Yin; Zhi, Joshua Ng Jun (Routledge, 2025)
"This book provides detailed case studies exploring how industry-leading organizations are integrating corporate innovation and sustainability initiatives. The book first introduces the difficulties and importance of managing innovation within established organizations. It identifies five themes key for organizations seeking to future-proof their business: external drivers in the business environment, structures for corporate entrepreneurship, modes of collaboration, sustainability as a lever for innovation, and performance management. It then provides detailed case studies of how companies across diverse sectors such as banking, shipping, and real estate, made the choice between short-term profit and future-proofing their business. Cases are written such that they can be used independently, and a storytelling approach is used so that readers may apply the conceptual frameworks and see how theories are translated into practice. Detailed teaching notes are available for instructors, each containing a sample lesson plan, six discussion questions, suggested answers, and further readings. A useful teaching resource for instructors and students in corporate entrepreneurship, corporate innovation, and strategic foresight"-- Provided by publisher.